2014
DOI: 10.1038/ejcn.2014.46
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence of cobalamin deficiency among vegetarians assessed by serum vitamin B12: a review of literature

Abstract: Individuals following vegetarian diets are at risk for developing vitamin B12 deficiency owing to suboptimal intake. As vitamin B12 is essential for the synthesis of nucleic acids, erythrocytes and in the maintenance of myelin, deficiency may result in a variety of symptoms. Some of these symptoms may be severe while others may be irreversible. The objective of this review was to assess vitamin B12 deficiency, based on reported serum vitamin B12, among individuals adhering to different types of vegetarian diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
2
15

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(206 citation statements)
references
References 44 publications
12
177
2
15
Order By: Relevance
“…Overall, these have shown that a wellplanned vegetarian or vegan diet can supply all the nutrients required for good health (6) . However, some concern remains over the possibility of low intakes of some nutrients such as vitamin B 12 , vitamin D, calcium and n-3 fatty acids in poorly selected and/or unfortified vegetarian or vegan diets (7,8) ; in particular, vitamin B 12 status has been widely observed to be relatively low in vegetarians and especially in vegans, and this is associated with relatively high plasma homocysteine (9) . Many studies have assessed health-related factors such as BMI, plasma cholesterol concentrations and blood pressure in vegetarians, but relatively few studies have been of sufficient magnitude and duration to examine the long-term health of vegetarians and vegans.…”
mentioning
confidence: 99%
“…Overall, these have shown that a wellplanned vegetarian or vegan diet can supply all the nutrients required for good health (6) . However, some concern remains over the possibility of low intakes of some nutrients such as vitamin B 12 , vitamin D, calcium and n-3 fatty acids in poorly selected and/or unfortified vegetarian or vegan diets (7,8) ; in particular, vitamin B 12 status has been widely observed to be relatively low in vegetarians and especially in vegans, and this is associated with relatively high plasma homocysteine (9) . Many studies have assessed health-related factors such as BMI, plasma cholesterol concentrations and blood pressure in vegetarians, but relatively few studies have been of sufficient magnitude and duration to examine the long-term health of vegetarians and vegans.…”
mentioning
confidence: 99%
“…Prevalence of Vitamin B12 deficiency among vegetarians is high with vegans more deficient compared to other vegetarians. 10 So it is important that the pure vegetarians should have a diet rich in vitamin B12, like legumes and milk.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalamin deficiency may result in a variety of symptoms, since vitamin B12 is essential for nucleic acid synthesis, erythrocytes and for the maintenance of myelin. 2 Neurological symptoms such as hypotonia, seizures and developmental delay can be seen in infants, while in older children megaloblastic hematological changings, extrapyramidal signs and delirium or psychosis can be observed. 3 Selective vitamin B12 malabsorption or Gräsbeck-Imerslund syndrome has been reported together with proteinuria 4 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Selective vitamin B12 malabsorption or Gräsbeck-Imerslund syndrome has been reported together with proteinuria 4 . In addition, if CD advances, it will cause anemia, 2 which may lead to chronic hypoxia as one of the causes of kidney injury. 5 Although hematological and neurological aspects of CD have been investigated extensively, there is no study on renal effects of CD in the literature search.…”
Section: Introductionmentioning
confidence: 99%